Enteric Myocarditis: A Case Report (Ibrahim Medical College Journal, 2009)
Enteric fever commonly causes fatality from abdominal complications or toxemia but it can also cause death from complications of myocarditis albeit rarely. In September, 2005 a 22 year old man was admitted in BIRDEM with the features of pneumonia. Later on, the patient developed acute left ventricular failure and ultimately diagnosed as a case of drug resistant enteric fever with myocarditis Ibrahim Med. Coll. J. 2007; 1(1): 34-37 Key words: Enteric fever; abdominal complications doi: 10.3329/imcj.v1i1.2893